Iodine quantification to characterize primary lesions, metastatic and non-metastatic lymph nodes in lung cancers by dual energy computed tomography: An initial experience. Issue 6 (June 2016) - Li, Xubin; Meng, Xiaoyan; Ye, Zhaoxiang
Abstract: Purpose: To investigate whether dual energy computed tomography (CT) with iodine quantification can characterize primary lesions and metastatic lymph nodes from non-metastatic ones in non-small cell lung cancer (NSCLC). Materials and methods: Sixty-one patients with NSCLC confirmed by pathology underwent chest contrast CT scan with dual energy computed tomography before surgery. The Iodine concentration (IC) and normalized iodine concentration (NIC) values of the primary lesions, 20 metastatic and 20 non-metastatic lymph nodes were measured, respectively. The differences between the primary lesions, metastatic and non-metastatic lymph nodes were statistically analyzed. Results: For the IC and NIC values of the primary lesions and their metastatic lymph nodes, there were no significant differences between lung squamous cell carcinomas and adenocarcinomas, respectively ( P > 0.05), while significant differences existed between metastatic and non-metastatic lymph nodes, respectively ( P < 0.05). The IC of 29.32 100 μg/cm 3 and NIC value of 0.4328 of a lymph node represented the optimal threshold to discriminate metastatic from non-metastatic lymph nodes and yielded the following: sensitivity, 80% and 75%; specificity, 65% and 75%; PPV, 70% and 75%; NPV, 76% and 75%; accuracy, 73% and 75%, respectively. Conclusion: Although its value in distinguishing primary lesions and their metastatic lymph nodes in NSCLC needs to be verified in further studies, dual energy CT with iodine quantification may be used to differentiate metastatic from non-metastatic lymph nodes in NSCLC.